Antibody-mediated rejection after lung transplantation - Bery, Amit I. (Ann Transl Med, 2020)
Antibody-mediated rejection (AMR) has been identified as a significant form of acute allograft dysfunction in lung transplantation. The development of consensus diagnostic criteria has created a uniform definition of AMR; however, significant limitations of these criteria have been identified. Treatment modalities for AMR have been adapted from other areas of medicine and data on the effectiveness of these therapies in AMR are limited. AMR is often refractory to these therapies, and graft failure and death are common. AMR is associated with increased rates of chronic lung allograft dysfunction (CLAD) and poor long-term survival. In this review, we discuss the history of AMR and describe known mechanisms, application of the consensus diagnostic criteria, data for current treatment strategies, and long-term outcomes. In addition, we highlight current gaps in knowledge, ongoing research, and future directions to address these gaps. Promising diagnostic techniques are actively being investigated that may allow for early detection and treatment of AMR. We conclude that further investigation is required to identify and define chronic and subclinical AMR, and head-to-head comparisons of currently used treatment protocols are necessary to identify an optimal treatment approach. Gaps in knowledge regarding the epidemiology, mechanisms, diagnosis, and treatment of AMR continue to exist and future research should focus on these aspects.